2008
DOI: 10.1007/s10585-008-9152-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteome analysis for profiling protein markers associated with carcinogenesis and lymph node metastasis in nasopharyngeal carcinoma

Abstract: Nasopharyngeal carcinoma (NPC), one of the most common cancers in population with Chinese or Asian progeny, poses a serious health problem for southern China. It is unfortunate that most NPC victims have had lymph node metastasis (LNM) when first diagnosed. We believe that the 2D based serum proteome analysis can be useful in discovering new biomarkers that may aid in the diagnosis and therapy of NPC patients. To filter the tumor specific antigen markers of NPC, sera from 42 healthy volunteers, 27 non-LNM NPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 62 publications
(63 reference statements)
0
20
1
Order By: Relevance
“…The method, unlike those involving the use of the CMB lectin, exclusively detected four additional serum proteins but the expression of the proteins was not significantly different between patients and controls. In contrast to our data, Liao et al reported the differential expression of 23 protein spots, 13 of which were identified by MS, in serum samples of NPC patients compared with the controls when their pooled serum samples were similarly subjected to albumin and IgG depletion [21]. Detection of considerably more serum proteins with altered expression may be due to a different sample pretreatment approach involving sonication to liberate proteins that were bound to albumin and IgG prior to their depletion.…”
Section: Discussioncontrasting
confidence: 99%
“…The method, unlike those involving the use of the CMB lectin, exclusively detected four additional serum proteins but the expression of the proteins was not significantly different between patients and controls. In contrast to our data, Liao et al reported the differential expression of 23 protein spots, 13 of which were identified by MS, in serum samples of NPC patients compared with the controls when their pooled serum samples were similarly subjected to albumin and IgG depletion [21]. Detection of considerably more serum proteins with altered expression may be due to a different sample pretreatment approach involving sonication to liberate proteins that were bound to albumin and IgG prior to their depletion.…”
Section: Discussioncontrasting
confidence: 99%
“…Traditionally, proteomic analysis of complex protein samples involves the separation of proteins by 2-DE, followed by protein identification using MS [11,12]. Using 2-DE comparative proteome analysis of tissues specimens or serum samples, researchers have identified several proteins as potential NPC biomarkers, such as stathmin, 14-3-3sigma, annexin I, HSP70, and sICAM-1 [13,14]. The difficulties with this approach include issues related to reproducibility, inter-gel variation and excessive time/labor cost, as well as poor representation of low-abundance proteins, highly acidic/basic proteins, or proteins with extreme size/hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated expression level of SAA has been reported in many types of cancers including: nasopharyngeal cancer [15][16][17], ovarian cancer [3,11,18], lung cancer [19][20][21][22], pancreatic cancer [23][24][25], prostate cancer [26][27][28], colorectal cancer [29,30], breast cancer [31,32], gastric cancer [33], pediatric osteosarcoma [34], neuroblastoma [35] and renal cell carcinoma [36,37] and other diseases such as amyloidosis, coronary artery disease, rheumatoid arthritis and severe acute respiratory syndrome [38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 99%